Short distances dominate connectivity patterns of coral communities in the North-West Arabian Sea - Michel R. Claereboudt; Gerd Bruss (Frontiers in Marine Science)
Larval connectivity relies on the ability of coral larvae to disperse into the environment following ocean currents. At short timescales, larval connectivity plays a key role in the resilience of coral reefs, as it determines their capacity to regain structure and function after major disturbances. At longer time scales, larval connectivity controls the distribution and, ultimately, the biogeography of species. We used a Lagrangian stochastic model to simulate the transport routes of coral larvae released from the major reef communities of the Arabian Sea and Gulf of Oman. The model used surface currents from two independent global circulation models, and we simulated 120 scenarios, covering four years and three larval competency models. Additionally we determine mean flow fields and LCS structures based on 20 years of reanalysis data from a third model. Connectivity values—the proportion of larvae successfully transported from their natal reef to another reef—varied significantly across reefs and years due to mesoscale variability in ocean currents, yet both circulation models produced similar overall patterns of connectivity. The general flow of larvae was from northwest to southeast in the Gulf of Oman, and from southwest to northeast in the Arabian Sea. The exchange of larvae across Ras Al-Hadd between the coral communities of the Arabian Sea and those of the Gulf of Oman is very low. Local retention (self-seeding) was the most important larval source for most reefs (mean = 32.3% for spawning corals and 70.8% for brooding corals). All reefs received larvae from at least one other reef and several received larvae from as many as five other reefs. ANOVA indicated significant differences between brooding and spawning coral larvae, and between reefs. Differences between years depended on the reef or reproduction type. Some reefs (Daymaniyat Islands in the Gulf of Oman and Mirbat in the Arabian Sea) could be considered sources of larvae, as they proportionally produced more larvae that later settled successfully than the other reefs. The limited connectivity between the Gulf of Oman and Arabian Sea supports their biogeographic distinction based on species distribution.